NORMATIVE STUDY OF SPATIAL POLICY COUNTRY BORDER AREA IN MALUKU PROVINCE THAT IS INDEPENDENT AND COMPETITIVE - Kennedy, Posma Sariguna Johnson; Tobing, Suzanna Josephine L.; Lumbantoruan, Rutman (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
This paper aims to review the spatial policy country border area in Maluku Province, by conducting normative studies. We study various literature and regulations issued by the government. The main source of the Republic of Indonesia Presidential Regulation Number 33 of 2015 concerning Spatial Planning for State Border Areas in Maluku Province. National Strategic Activities Center (PKSN) and Priority Location (Lokpri) planning and development is expected to provide direction for the development of border areas in a comprehensive manner and become an input for the process of formulating border area development policies at the national, provincial and district levels so that is independent and competitive. Keywords: spatial policy country border, National Strategic Activities Center (PKSN), Priority Location (Lokpri), independent and competitive.